ADA AS MAIN BIOCHEMICAL MARKER IN PATIENTS WITH TUBERCULOUS EFFUSION: ADA in tuberculous effusion - Janković, Jelena; Ilic, Branislav; Đurđević, Nataša; Jandric, Aleksandar (Journal of Medical Biochemistry, 2023)
Tuberculous pleuritis (TP) is one of the most common extra-pulmonary tuberculosis form. Because of tuberculous pleurisy is hard to diagnose due to slow course of disease and lack of specificity in symptoms and diagnostic methods. In that reason, we need multidisciplinary approach and efficient biomarkers. Acid-fast bacilli (AFB) staining, cultures and pathophysiological biopsy finding from the majority of patients are positive only in less than 10%. Löwenstein culture results need time about 6-8 weeks what delays diagnosis. Adenosine deaminase (ADA) is biomarker with high sensitivity and specificity (more than 90%) and considered as gold standard of biomarkers in the diagnosis of TP. It is very hard to distinguish malignant from TP with lymphocyte predomination, but in patient with malignant pleural effusion the level of ADA is decreased, opposite from TP. ADA in pleural punctate is a fast, simple, efficient and economical way for clarification the etiology of the pleural effusion as tuberculous pleurisy. Also, many studies have proved the role of ADA in the response to treatment for tuberculosis at follow up period
Keywords: Adenosine deaminase; biomarkers; pleural effusion; tuberculosis